EUROPA: Has Anything New Been Learned With Angiotensin‐Converting Enzyme Inhibitors? - Sica, Domenic A (J Clin Hypertens (Greenwich), 2007)
The European Trial on Reduction of Cardiac Events with Perindopril in Stable Coronary Artery Disease (EUROPA) involved 12,218 patients with stable coronary artery disease. Patients in this trial were randomized to the angiotensin‐converting enzyme inhibitor perindopril (8 mg/d) or placebo in addition to optimized conventional therapy and followed for an average of 4 years. Perindopril reduced the primary end points of cardiovascular disease, myocardial infarction, and cardiac arrest by 20% (p=0.0003). Moreover, the angiotensin‐converting enzyme inhibitor reduced the rate of fatal and nonfatal myocardial infarction by 24% (p=0.001). The results from EUROPA complement those observed in the Heart Outcomes and Prevention Evaluation (HOPE) study and provide further support for the concept of angiotensin‐converting enzyme inhibitors conferring cardiovascular protection as a class effect.